The Hallmarks of Ageing in Human Immunodeficiency Virus Infection and the Impact of Antiretroviral Therapy on Telomeres: A Molecular Perspective - Miruna-Maria Apetroaei; Stella Baliou; Petros Ioannou; Persefoni Fragkiadaki; Gabriela Ștefan; Marina Ionela (Ilie) Nedea; George-Traian-Alexandru Burcea-Dragomiroiu; Bruno Ștefan Velescu; Anca Oana Docea; Denisa Ioana Udeanu; Aristidis Tsatsakis; Andreea Letiția Arsene (Current Issues in Molecular Biology)
Ageing is a complex and unavoidable physiological process which, in simple terms, consists of a progressive deterioration in the functionality of cells, tissues and organs, culminating in an increased risk of developing chronic pathologies. Telomeres, the repetitive nucleotide structures at the end of chromosomes, ensure genomic integrity and modulate cellular senescence. The progressive shortening of telomere length with each cell division directly correlates with an increased susceptibility to developing chronic pathologies. However, this shortening, normally physiological and inevitable, can be markedly accelerated in the presence of chronic infections, such as HIV-1 infection, by sustained and continuous activation of the immune system, chronic inflammation, generation of oxidative stress, or direct alterations produced by viral proteins. Thus, in this narrative review, we discuss the 12 hallmarks of ageing in the context of HIV-1 infection, as understanding the molecular changes induced by HIV-1 through these well-established pillars could provide a holistic approach to the management of HIV-positive patients. At the same time, considering that telomeres are at the centre of all these changes, an assessment of the impact of antiretroviral therapy on telomere length is necessary to guide clinical decisions. The ultimate goal of this research is to develop personalised therapies to increase the quality of life and health outcomes of HIV patients.